Model of Civic Education Learning Based on The Local Wisdom for Revitalizing Values of Pancasila - Bambang Sumardjoko; Muhamad Musyiam (LPMPP Universitas Negeri Yogyakarta, 2018)
Abstract: The objectives of this study are to describe the existing civic education learning, develop the model of civic education learning, and measure the effectiveness of the model of civic education learning based on the local wisdom. This research and development study was carried out in three stages, i.e., preliminary study, development, and model effectiveness test. The data in this study were collected through interview and observation. The results of the research are, first, there are strength, weaknesses, chances, and obstacles in civic education learning. Second, the development of the model of civic education learning based on the local wisdom is presented in the form of the syntax of learning model through the practice of cooperative learning of Problem Based Learning and Value Clarification. Third, the model of civic education learning can be categorized as “effective” based on the criteria of validity, practicality, and effectiveness. The model of civic education learning based on the local wisdom is able to improve the score of character and nation identity by 80% and the mastery learning at least 75%. Keywords: effectiveness of learning model, local wisdom, civics learningModel Pembelajaran Pendidikan Kewarganegaraan Berbasis Kearifan Lokal sebagai Strategi Revitalisasi Nilai-Nilai Pancasila Abstrak: Tujuan penulisan ini untuk mendeskripsikan pemataan pembelajaran PKn yang tengah berlangsung selama ini, pengembangan model pembelajaran PKn, dan efektivitas model pembelajaran PKn berbasis kearifan lokal. Data diperoleh melalui penelitian pengembangan, dimulai dari studi pendahuluan, pengembangan, dan uji efektivitas model. Hasil penelitian sebagai berikut, pertama, dalam pembelajaran PKn terdapat kekuatan, kelemahan, peluang, dan ancaman. Kedua, pengembangan model pembelajaran PKn berbasis kearifan lokal dikemas dalam sintak model pembelajaran, melalui praktik pembelajaran kooperatif Problem Based Learning dan Value Clarification. Ketiga, model pembelajaran PKn tergolong efektif berdasarkan kriteria kevalidan, kepraktisan, dan keefektifan. Model pembelajaran PKn berbasis kearifan lokal mampu meningkatkan skor karakter dan jati diri bangsa sebesar 80% serta ketuntasan belajar sekurang-kurangnya 75%.Kata kunci: efektivitas model pembelajaran, kearifan lokal, pembelajaran PKn